The Environmental Kuznets Curve Hypothesis in the United States: A Review - Mahmood, Haider; Houaneb, Amira (International Journal of Energy Economics and Policy, 2023)
The economy of the United States (US) is highly developed. However, the US stands second in the World as per total CO2 emissions and this economy has environmental problems. The Environmental Kuznets Curve (EKC) has been probed extensively in the US economy. However, a review study is missing in the US case. The present research has reviewed 60 papers on the EKC in the US. 41 studies have authenticated the EKC in the US economy. But, 19 papers did not substantiate it. 11 out of 60 studies used disaggregated state-level data and most of these studies validated the EKC. 49 papers investigated the EKC for aggregated US data and the probability of the existence of the EKC is found lower in these papers in contrast to disaggregated studies. Moreover, the EKC is substantiated in the 24 papers confirming a negative impact of Renewable Energy Consumption (REC) on emissions. Moreover, logistic regression is utilized to test these findings. The results confirm that the possibility of EKC is 3.0885 times more if a study validates a negative impact of REC on emissions. The effect of disaggregated data is found statistically insignificant on the EKC validation.